Annotated world checklist of the Trombiculidae and Leeuwenhoekiidae (1758–2021) (Acari: Trombiculoidea), with notes on nomenclature, taxonomy, and distribution - Nielsen, David H.; Robbins, Richard G.; Rueda, Leopoldo M. (Zootaxa, 2021)
The superfamily Trombiculoidea is a large and diverse group of acarines that comprises six families; of these, the families Trombiculidae and Leeuwenhoekiidae are characterized by larvae commonly known as chiggers that are parasites of terrestrial vertebrates, including humans, and some species are of medical importance as vectors of chigger-borne rickettsiosis (scrub typhus), caused by the rickettsia Orientia tsutsugamushi. This paper presents an annotated checklist of 3,013 generally accepted chigger species, together with their distribution by zoogeographic region, and a non-comprehensive list of synonyms. A total of 58 new combinations are proposed by transferring species to different genera, treating some subgenera as genera, or updating current generic names. The checklist updates earlier catalogs of the world chigger fauna, but because the literature on chigger taxonomy is voluminous and scattered, similar, regional monographs were utilized in constructing the classificatory foundation. This list may not contain every species, synonym or taxonomic rearrangement that has been published, but it reflects the most recent arrangement of chigger taxa. Distribution records are primarily drawn from collection sites listed in the original species descriptions, together with subsequently published geographical records.